Local Wisdom Based Social Responsibility of Balinese SME to Improve Competitiveness - Gunawan, Sandy; Syarief, Rizal; Nurhayati, Popong; Asnawi, Yudha Heryawan; Joewono, Handito Hadi (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Small and Medium Enterprises (SMEs) have crucial role in Indonesian economy. Despite the enormous contribution, SMEs still encounter obstacles in business development. SMEs do not yet have appropriate strategy to create competitiveness. Strategies suitable for SMEs must consider local wisdom of the location where SMEs domicile. This study aims to analyze the influence of local wisdom in creating competitiveness for SMEs, carried out through socially responsible practices. This study applies qualitative method focusing on twelve SMEs located in Badung district, Bali. Information was obtained through in-depth interviews and literature review. The information was analyzed to determine the relation between local wisdom values and the concept of social responsibility. This research proves that local wisdom has influence in creating competitive advantage through socially responsible business practices. The value triggers the SMEs to be socially responsible towards its customers, employees, environment and community that in return improve its reputation, customers’ satisfaction, employees’ loyalty and productivity. Keywords: competitiveness, local wisdom, smes, social responsibility, strategy